Penerapan Teknologi IoT untuk Absensi Organisasi Mahasiswa Menggunakan RFID dan Web Dashboard - Muhamad Rafi Hermansah (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The development of Internet of Things (IoT) technology provides great opportunities for automating attendance systems in organizations. This study aims to design and implement an attendance system based on RFID (Radio Frequency Identification) with data storage using a MySQL database. The system utilizes an ESP32 microcontroller to read RFID cards and send attendance data to a server via the HTTP protocol. The server, built with PHP, processes and stores the data in MySQL in real time. A web dashboard developed using HTML, CSS, and JavaScript displays attendance information and provides a report export feature in PDF format. The implementation results show that the system records attendance quickly and accurately while minimizing fraud such as proxy attendance. The application of IoT integrated with MySQL proves effective in supporting efficiency, transparency, and the digitalization of organizational attendance management